Interface Controlled Materials 2000
DOI: 10.1002/352760622x.ch16
|View full text |Cite
|
Sign up to set email alerts
|

On the Physical Nature of Traps in Polycrystalline Sb 2 O 3

Abstract: IntroductionTwo types of carrier traps are observed in several organic and anorganic compounds : traps whit discrete energy level in forbidden band of the crystal and traps whit a quasi -continuous distribution of energy levels having the maximum density at the density at the edge of the conduction or valence band. Both types of traps have been found and extensively investigated in molecular organic crystal. Simultaneous presence of both types of carrier traps have been observed also in a number of polycrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This is in good agreement with SEM analysis. All thin films exhibited semiconducting behaviors with the conductivity range 10 À7 -10 À9 O À1 / cm [12,13,15]. The conductivity of the films was found to increase from 1.54 Â 10 À9 to 1.06 Â 10 À7 O À1 /cm when the substrate temperature increases from 300 to 573 K. This increase may be attributed to the structural characteristics of films.…”
Section: Article In Pressmentioning
confidence: 83%
See 1 more Smart Citation
“…This is in good agreement with SEM analysis. All thin films exhibited semiconducting behaviors with the conductivity range 10 À7 -10 À9 O À1 / cm [12,13,15]. The conductivity of the films was found to increase from 1.54 Â 10 À9 to 1.06 Â 10 À7 O À1 /cm when the substrate temperature increases from 300 to 573 K. This increase may be attributed to the structural characteristics of films.…”
Section: Article In Pressmentioning
confidence: 83%
“…The UV-VIS-NIR transmission spectrum studies showed that the bandgap of Sb 2 O 3 thin films (3.62 eV) is much larger than that in orthorhombic crystal of Sb 2 O 3 (3.30 eV) [9,10]. In a series of previous papers [11][12][13][14][15] we have studied the electrical and optical properties of Sb 2 O 3 thin films prepared by thermal evaporation method. However, no detailed study is reported of the structural properties of these thin films.…”
Section: Introductionmentioning
confidence: 98%